Comparison of Haematologic parameters among adolescents with and without asymptomatic malaria in Ibadan, Nigeria (2022)
Background and Objectives: Asymptomatic malaria results from partial immunity resulting from recurrent exposure to the malaria parasite and it has been shown not to be benign as it was earlier believed. Adolescents are likely to have partial immunity to malaria which can predispose them to the asymptomatic form of malaria, but malaria is understudied in this age group. This study was conducted to compare the haematologic parameters among secondary school adolescents with and without asymptomatic malaria in Ibadan. Methods: A cross-sectional study was conducted and data regarding sociodemographic characteristics, presence or otherwise of malaria parasite (using microscopy) and haematological parameters (obtained using haematology auto- analyser and microscopy) were documented. Malaria parasite density was categorised as 1-100 and >100/μL. Other haematological parameters were classified as categorical variables. Associations were determined using Chi square test and level of significance was p<0.05. Results: A total of 103 students were recruited with a mean age of 15.6±2.02 years and 61(59.2%) were boys. Those from the low socioeconomic class were 86 (83.5%), 24 (23.3%) had asymptomatic malaria while 22 (21.4%) had parasite density of >100/μL. Haematological abnormalities detected were anaemia (11.7%), leucopenia (4.9%), thrombocytopenia (11.7%), reduced MCV and reduced MCH (88.3%). All participants had low MCHC. Abnormal peripheral blood film was found in 79.5% but this was not associated with the presence of malaria parasite. Older adolescence (age ≥ 15 years) was significantly associated with parasite density of>100/μL (p = 0.02) and a higher proportion of those from the low socioeconomic class had asymptomatic malaria (24.4% vs 17.6%). Conclusion: Although some haematologic parameters of the study participants were affected by asymptomatic malaria, there were other unexplained blood abnormalities. There is a need to address asymptomatic malaria among these adolescents and other causes of abnormal blood profile should be tackled.